Front Line Surgery A Practical Approach - Martin, Matthew J.; Beekley, Alec C.; Eckert, Matthew J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
The second edition of Front Line Surgery expands upon the success of the first edition, providing updated discussion of practical management of commonly encountered combat injuries.This edition reflects the cutting edge of combat casualty care, refined principles of surgical management of specific injury patterns, and incorporation of the spectrum of recent research advancements in trauma care. Each chapter continues to follow the same organization as the first edition. The (3z(BBLUF(3y(B, or bottom line up front, headlines each topic, providing the critical pearls for the reader, followed by a focused and straight forward discussion of management, pitfalls, and recommendations. In addition, select chapters conclude with a section discussing the application of this topic in civilian practice, as potentially encountered by the rural or humanitarian relief surgeon. Additional new topics include: REBOA and endovascular techniques for hemorrhage control, updates in transfusion and resuscitation practice, active shooter situations, rural trauma management in developed nations, advancements in prehospital care and the Tactical Combat Casualty Care (TC3) course, and discussion of the newest generations of topical hemostatic agents and tourniquets. These additions serve to both enhance the breadth and depth of the material relevant to military surgeons, but should also further expand the applicability and interest in this work to all civilian trauma surgeons.s
Tactical Combat Casualty Care -- Combat Triage and Mass Casualty Management -- Initial Management Priorities: Beyond ABCDE -- Damage Control Resuscitation -- To Operate or Image? (Pulling the Trigger) -- Ultrasound in Combat Trauma -- The Bowel: Contamination, Colostomies, and Combat Surgery -- Liver and Spleen Injury Management in Combat -- Pancreatic and Duodenal Injuries (Don$1 (Bt Mess with the$1! =(B) -- Operative Management of Renal Injuries -- Major Abdominal Vascular Trauma -- To Close or Not to Close: Managing the Open Abdomen -- Dismounted Complex Blast Injury Management -- Thoracic Approaches and Incisions -- Lung Injuries in Combat -- Diagnosis and Management of Penetrating Cardiac Injury -- Thoracic Vascular Injuries: Operative Management in (3z(BEnemy(3y (BTerritory -- Chest Wall and Diaphragm Injury -- Soft Tissue Wounds and Fasciotomies -- Extremity Fractures and the Mangled Extremity -- Traumatic Amputations -- Peripheral Vascular Injuries -- The Neck -- Genitourinary Injuries (Excluding Kidney) -- Neurosurgery for Dummies -- Traumatic Brain Injury and Neurocritical Care -- Spine Injuries -- Face and Head (Non-Ocular) Injury -- Managing Eye Trauma in the Combat Environment -- Burn Care in the Deployed Setting -- The Pediatric Patient in Wartime -- The Combat Hospital ICU -- Postoperative Resuscitation -- TEG/ROTEM Driven Resuscitation in Trauma -- Monitoring -- Ventilator Management: A Practical Approach to Respiratory Failure in Combat -- Practical Approach to Combat-Related Infections and Antibiotics -- Patient Transfer, En-route Care, and Critical Care Air Transport Team (CCATT) -- The Homefront: Role 4 and 5 Care -- Active Shooter and Intentional Mass Casualty Events -- Tactical Emergency Casualty Care (TECC): Principles and Practice -- Humanitarian and Local National Care -- Expectant and End of Life Care in a Combat Zone -- Trauma System Development and the Joint Trauma System -- The Next Generation of Hemorrhage Therapy -- Resident Readiness and Training the Surgeon for Battlefield Care -- The Deployed Advanced Care Provider -- Military Civilian Collaboration for National Preparedness During Peace and War -- Battlefield Resuscitation of the Future -- Non-Conventional Forward Surgical Elements -- Appendix A. Improvise, Adapt, Overcome: Field Expedient Methods in a Forward Environment -- Appendix B. Burn Charts and Orders -- Appendix C. Resources, References, and Readiness -- Appendix D. (3z(BC(3y (BBNRE Primer for Surgeons.s
Keywords: Medicine; Emergency medicine; Surgery; Abdominal surgery; Thoracic surgery; Traumatology; Medicine & Public Health; Surgery; Abdominal surgery; General Surgery; Thoracic surgery; Traumatic Surgery; Emergency medicine